Highly efficient RNA-guided base editing in rabbit - Liu, Zhiquan; Chen, Mao; Chen, Siyu; Deng, Jichao; Song, Yuning; Lai, Liangxue; Li, Zhanjun (Nature communications, 2018)
Cytidine base editors (CBEs) and adenine base editors (ABEs), composed of a cytidine deaminase or an evolved adenine deaminase fused to Cas9 nickase, enable the conversion of C·G to T·A or A·T to G·C base pair in organisms, respectively. Here, we show that BE3 and ABE7.10 systems can achieve a targeted mutation efficiency of 53–88% and 44–100%, respectively, in both blastocysts and Founder (F0) rabbits. Meanwhile, this strategy can be used to precisely mimic human pathologies by efficiently inducing nonsense or missense mutations as well as RNA mis-splicing in rabbit. In addition, the reduced frequencies of indels with higher product purity are also determined in rabbit blastocysts by BE4-Gam, which is an updated version of the BE3 system. Collectively, this work provides a simple and efficient method for targeted point mutations and generation of disease models in rabbit. Base editors can make targeted changes without inducing a double-stranded break. Here, the authors apply the BE3 and ABE7.10 systems to rabbit to create highly efficient targeted base substitutions and various mutation types, and show reduced frequency of undesired by-products with the updated BE4-Gam system.